A comparison of online and offline gender and goal directed shopping online. (September 2017) - Davis, Robert; Smith, Sandra D.; Lang, Bodo U.
Abstract: The aim of this paper is to model the effect of the consumers' perceptions of their offline and online gendered behaviour on online utilitarian shopping motivation and purchase intentions. We hypothesise that when consumers shop online, their behaviour is mediated by two gendered behaviours, namely offline and online. To test this hypothesis, 515 usable responses were collected in face-to-face interviews. The conceptual model was tested with confirmatory factors analysis (CFA) and structural equation modelling (SEM) across five product categories. Our findings show that the effect of a consumer's perception of their gendered behaviour offline vs. online on online utilitarian shopping motivation and purchase intentions is significantly different. In particular we found that utilitarian shopping motivation online has a significant effect on purchase intentions online mediated by gender (online) overall: strongly for females but not for males . Conversely, utilitarian shopping motivation online has a significant effect on purchase intentions online mediated by gender (offline) for males but not overall and for females . Highlights: Models the impact of consumers' offline and online gendered behaviour. Uses 515 responses from consumers collected via face-to-face interviews. Data spans five product categories. Employs confirmatory factors analysis and structural equation modelling. Consumers online shopping is mediated by two gendered behaviours: offline and online.